Adaptive Output Feedback Controller of Voltage Source Inverters in Microgrid Connected Mode. Issue 2 (2020) - Ammeh, L.; Fadil, H. El; Oulcaid, M.; Giri, F.; Ahmed-Ali, T.
Abstract: This paper deals with the control of Voltage Source Inverters (VSIs) connected to the main grid. The controller aim is fourfold: i) enforcing the current injected by the VSI to follow a given reference, ii) estimating the grid resistance and inductance, iii) estimating the current load and the grid voltage, iv) assuming an asymptotic stability of the system. To achieve these aims, we designed an adaptive output feedback controller using the backstepping technique and the high gain approach. Moreover, the controller has the ability to compensate the reactive power of the local load. The system stability was analyzed by Lyapunov theory. The controller performances were illustrated by simulations with grid parameter and load current variations.